2021
DOI: 10.1063/5.0063385
|View full text |Cite
|
Sign up to set email alerts
|

Composition dependencies of crystal structure and electrical properties of epitaxial tetragonal (Bi, Na)TiO3–BaTiO3 films grown on (100)cSrRuO3//(100)SrTiO3 substrates by pulsed laser depositions

Abstract: Lead-free piezoelectric (1 − x)(Bi, Na)TiO3–xBaTiO3 (x = 0.06–1.0) thin films were deposited, and their crystal structures, ferroelectricity, and piezoelectric properties were studied. These films were epitaxially grown on SrRuO3 covered (100) SrTiO3 substrates by pulsed laser deposition using ceramic targets. For all the compositions, the tetragonal films were found to be grown with (001), polar-axis orientation, mainly due to the thermal strain caused by the different thermal expansion coefficients between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In contrast, the film on SrTiO 3 is an epitaxial film, for which detailed XRD analysis was performed in the previous study. 47 The domain fraction of the ferroelectric film is determined by the thermal strain from the substrate. The Si substrate has a lower thermal expansion coefficient, 3.7 × 10 6 /K, 48 than BNT-BT, ∼6 × 10 6 /K, 35 whereas the value for the SrTiO 3 substrate is higher, 10.0 × 10 6 /K.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the film on SrTiO 3 is an epitaxial film, for which detailed XRD analysis was performed in the previous study. 47 The domain fraction of the ferroelectric film is determined by the thermal strain from the substrate. The Si substrate has a lower thermal expansion coefficient, 3.7 × 10 6 /K, 48 than BNT-BT, ∼6 × 10 6 /K, 35 whereas the value for the SrTiO 3 substrate is higher, 10.0 × 10 6 /K.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The tetragonal lattice parameters of 0.7BNT-0.3BT were reported to be approximately 3.92 and 4.01 Å for the a -axis and c -axis, respectively, suggesting that the majority domains are the a -domain and c -domain for the films on Si and SrTiO 3 , respectively, from the powder XRD. , BNT-BT on the Si substrate has an out-of-plane (100)-orientation with the in-plane random orientation, confirmed by X-ray pole figure measurement shown in Figure . In contrast, the film on SrTiO 3 is an epitaxial film, for which detailed XRD analysis was performed in the previous study . The domain fraction of the ferroelectric film is determined by the thermal strain from the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…The P r of the films was smaller than those reported for ceramics and c -axis oriented films on SrTiO 3 substrates. 39 , 41 This is mainly due to the a -axis orientation of these films and suppressed tetragonality in comparison with bulk ceramics, as shown in Figure 2 (b). 39 Furthermore, comparing the data for the first and second cycles of sweep-up in Figure 4 (c) revealed that the films with x = 0.2, 0.3, and 0.5 exhibit a “two-step increase” in P r value, as confirmed from the data presented in Figures 3 and S2 .…”
Section: Resultsmentioning
confidence: 88%
“…According to our previous reports, tetragonal (Bi,Na)TiO 3 –BaTiO 3 films ( x = 0.06–1.0) deposited on SrTiO 3 substrates are epitaxial films and were subjected to detailed XRD analysis. 41 , 42 These results show that the volume fraction of the (100) orientation and non-180° domain fraction of the (100)/(001)-oriented ferroelectric films are determined by the thermal strain from the substrate; the thermal expansion coefficient of the SrTiO 3 substrate is 10.9 × 10 –6 /K, 43 which is larger than that of (Bi,Na)TiO 3 –BaTiO 3 (approximately 6 × 10 –6 /K). 33 Thus, the (Bi,Na)TiO 3 –BaTiO 3 film on the SrTiO 3 substrate was confirmed to have a pure (001) orientation and c -domain structure with a polarization axis along the out-of-plane direction, which can be attributed to the in-plane compressive strain experienced during the cooling process after deposition.…”
Section: Resultsmentioning
confidence: 99%
“…S2 †). The higher E C of the bilayer may be associated with a larger in-plane compressive strain 39,40 and more defects, such as oxygen vacancies (Fig. S4 †), which can pin the switch of ferroelectric domains.…”
Section: Ferroelectricitymentioning
confidence: 99%